Literacy crises and reading policies : children still can't read! - Soler, Janet (Routledge, 2006)
The authors build a convincing case that the problem of how to teach reading needs to be re-conceptualized as part of a deeply social phenomenon. The study addresses the critical issue of literacy crises around the world and questions their wider sociological and educational impact.